Cool by association: examining the impact of influencers on brand coolness - Rekiö, Jenna-Juulia (2024)
In this master's thesis, the components of brand coolness and the significance of social media influencers in perceived brand coolness were investigated. The aim was to enhance understanding of the meanings brand coolness and influencer-brand relationships hold from the consumers' perspective.